Approaches to treating pain in terms of the mechanisms of its development - Galina Rashidovna Imametdinova; N V Chichasova; E V Igolkina (Современная ревматология)
The paper considers problems in the treatment of acute and chronic pain in patients with rheumatic diseases and shows the role of inflammation and muscle spasm in the pathogenesis of acute and chronic pain. It gives the results of clinical trials and the clinical use of nimesulide (Nise ®) and tizanidine (Sirdalud ®) in the treatment of acute and chronic pain.